Shape Alterations of Subcortical Nuclei Correlate With Amyotrophic Lateral Sclerosis Progression - Yanchun Yuan; Yan Fu; Xueying Wang; Fan Hu; Qianqian Zhao; Cailin He; Linxin Tang; Yongchao Li; Yue Bu; Xinyu Song; Qing Liu; Ziqin Liu; et al. (Brain and Behavior)
ABSTRACT Background Neuroimaging has been increasingly used to assess brain structural alterations in patients with amyotrophic lateral sclerosis (ALS). We aimed to investigate alterations in brain sub‐cortical structures and to identify potential neuroimaging biomarkers for disease progression for patients with ALS. Methods A total of 61 patients with ALS were prospectively enrolled and were divided into three subgroups according to disease progression, i.e., fast, intermediate, and slow progression. Sixty‐one matched healthy controls (HCs) were also recruited. All participants acquired a brain structural magnetic resonance imaging scan for subcortical volumetric and shape analyses. Neuropsychological testing and functional assessment were performed. Results Patients with fast progression showed significant shape alterations in basal ganglia and brainstem as compared to the HCs group. In ALS patients with fast progression, shape contractions with atrophic changes were noted in bilateral nucleus accumbens, left caudate, left thalamus, and brainstem; while shape expansion with hypertrophy was noted in the left caudate, left thalamus, and left pallidum (all p < 0.05). There were significant positive correlations of the shape changes of the left thalamus with the Amyotrophic Lateral Sclerosis Functional Rating Scale‐Revised (ALS‐FRS‐R) total and limb scores and with disease duration (all p < 0.05). There were positive correlations of left pallidum with anxiety or with disease duration, and of left nucleus accumbens with ALS‐FRS‐R total or bulbar score, and of brainstem with mini‐mental state examination score (all p < 0.05). Conclusion Extensive shape alterations of subcortical nuclei were noted in patients with fast progression of ALS, implicating subcortical shape being a potential neuroimaging biomarker for ALS progression.